2002
DOI: 10.1034/j.1398-9995.2002.1oxxx.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and allergy: the significance of chronic conditions for individual health behaviour

Abstract: Background: In health economics, health is regarded as part of an individual's human capital. As such it depreciates over time, and investments in health are made in order to keep the stock of health capital at the desired level. Using this framework for analysis of health-related behaviour and Swedish panel data, we examined whether the presence of asthma or allergy affects perceived health and investments in health. Methods: A set of panel data for approximately 3800 individuals interviewed repeatedly in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Studies have generally shown that people with asthma or other chronic conditions perceive their health to be lower than the general population (13)(14)(15). This is perhaps not surprising given that they have a chronic health problem; however, many other individuals with chronic conditions perceive their health to be very good or excellent, (15,16) suggesting that the presence of a chronic condition is not enough, in and of itself, to predict lower levels of perceived health.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have generally shown that people with asthma or other chronic conditions perceive their health to be lower than the general population (13)(14)(15). This is perhaps not surprising given that they have a chronic health problem; however, many other individuals with chronic conditions perceive their health to be very good or excellent, (15,16) suggesting that the presence of a chronic condition is not enough, in and of itself, to predict lower levels of perceived health.…”
Section: Discussionmentioning
confidence: 90%
“…For diabetes, the review by Milton and colleagues concluded, based on mostly smallsample studies, that persons with childhood onset of diabetes would experience lower employment rates and income following diabetic complications [9]. Nevertheless, correlations do not imply causation, and the role of education as a determinant of health, that is, that the effect proceeds from education to health, has been extensively analysed [45,46]. While this direction is relevant for lifestyle-related diseases, for example, or analyses of disease management, our analysis concerns the effect of an unanticipated, significant, health-related life event and its effect on labour-market outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Grossman model has been estimated empirically both for the general population in various countries and for a specific sub-population, individuals suffering from asthma or allergy in Sweden, and the evidence has been broadly supportive [23][24][25][26][27].…”
Section: Theoretical Frameworkmentioning
confidence: 98%